Dialogue It's Condition ,instractions and obstacles (Journal of the College of Basic Education, 2026)
Dialogue is a noble human value that we must preserve and strive to establish in our homes, schools, universities, and in our public and private institutions, and in our interactions with others in the broad sense—those who differ from us in many ways. It is the ideal way to change wrong concepts, correct deviant ideas, and straighten misbehaviors.Reasons for Choosing the Topic:Dialogue is one of the most important manifestations of civilization and acceptance of others in its broadest sense, and the desire to communicate with them for the good and interest of all.Dialogue enhances self-confidence and conviction in what one believes to be right, and removes fear of openness to others.Dialogue is a necessity of life, not an intellectual luxury as some practice it.Importance of the Research:Dialogue is one of the most important methods that can be used in the field of calling to Allah Almighty and in correcting wrong concepts.It is one of the most successful educational methods and a way to instill virtuous values and good morals in the hearts of the youth.Dialogue is a prophetic approach in how the Prophet (peace be upon him) dealt with his family, companions, and enemies.Research Problem:The vast majority of people do not engage in dialogue with someone they dislike and avoid them because they see them as arrogant and contemptuous. Some, out of pride and arrogance, do not engage in dialogue with others because they feel they are of lower status and rank.